P192 Acute non-invasive ventilation: a survey of medical registrars. (December 2018) - Sagar, D; Brett, C; Highcock, M
Abstract : Introduction: The 2017 National Confidential Enquiry into Patient Outcome and Death identified shortcomings in the provision of acute Non-invasive Ventilation (NIV) in the U.K. 1 In response, the British Thoracic Society published draft quality standards for public consultation in August 2017. 2 These state that all involved staff should have evidence of training. We explored the provision of training and other aspects of the NIV service within our region via an electronic questionnaire. Methods: All 465 General Internal Medicine (GIM) registrars in our region were notified via email and encouraged to complete an online survey, between the 27th October and 11th December 2017. Questions addressed the local arrangements for providing treatment, the training received by responders and their attitudes and confidence in delivering therapy. Results: 79 responses were received. 40 responders worked in a district general hospital, 39 in a teaching hospital. 24 were respiratory trainees, 13 were acute medical trainees and 42 were other GIM trainees. 71 were actively involved in the acute medical take. 42 commented that the decision to start treatment was made by the on-call medical registrars. 3 of 37 respiratory/acute medical trainees had not had NIV training compared to 20 of 42 trainees from other specialities. Only one respiratory/acute medicine trainee admitted to a lack of confidence in selecting patients with COPD for treatment, compared with 9 in the other group. 9 respiratory/acute medicine trainees admitted to incomplete confidence in adjusting machine settings, compared with 33 in the other group. 11 responders would use NIV in Asthma, 25 in Idiopathic Pulmonary Fibrosis and 28 in Pneumonia, in contrast to published guidelines. Conclusions: Acute NIV is frequently delivered by GIM registrars. Not all are given specific training and this is most marked in non-respiratory/acute medicine trainees. Acute NIV should be a separate and clear domain in the GIM Curriculum for registrars and form part of the Annual Review of Competence Progression requirements. Inadequate training may be contributing to the use of NIV in inappropriate clinical circumstances. References: NCEPOD – Non-Invasive Ventilation: Inspiring Change2017. BTS: Quality Standards for Non-invasive ventilation.